181k views
2 votes
E^2x -2e^x -8=0

{e}^(2x) - {2e}^(x) - 8 = 0

User Nessie
by
5.5k points

1 Answer

5 votes
E^2x -2e^x -8=0 => e^(2x) -2e^x -8=0

Temporarily replace e^x with y.

Then (y)^2 - 2y - 8 = 0. Factors are (y-4) and (y+2).

Roots are y = 4 and y= -2.

Now remembering that we temporarily replaced e^x with y, we let
y=4 = e^x. We need to solve for x. Taking the natural log of both sides, we get:

ln 4 = x (answer)

We have to discard the other root (y= -2), because we cannot take the ln of a negative number.


User Kcstricks
by
5.7k points